Il saluto di Milano (Materiali di Estetica. Terza serie, 2019)
This short contribution traces the deep bond between Dorfles and the city of Milan as early as 1928, the year in which the city welcomed him. Eclectic protagonist of Milanese cultural life in the twentieth century, Dorfles remains one of the leading interpreters of the passion for the contemporary that has always distinguished his private and public life.